PERLINDUNGAN HUKUM TERHADAP PEREMPUAN DARI KEKERASAN PSIKIS DALAM RUMAH TANGGA - N.N. Adiyaryani; I.G. Artha; I.G.A.A. Krisnawati; I.D.G.D. Sugama (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Domestic violence mainly causes female victims.This activity aims to determine the understanding of women in Cau Belayu village, Marga District,Tabanan Regency about the existence of legal protection for women who experience domestic violence, the existence of legal protection for women who experience psychological violence and procedures settlement of cases of psychological violence in the household. The methods used are lectures, sharing and discussions. Many women in Cau Beayu Village, Tabanan Regency already know about the lack of laws that provide protection to women who experience domestic violence but need to given a more detailed explanation regarding the forms of legal protection provided to women who experience psychological violence in the household and procedures for resolving cases of psychological violence experienced by women within the household, either through existing legal channels or through social institutions that care about women and domestic violence. Keywords: legal protection, domestic violence, psychological violence.